2016
DOI: 10.1371/journal.pone.0145647
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MTAP Gene Expression in Breast Cancer Patients and Cell Lines

Abstract: MTAP is a ubiquitously expressed gene important for adenine and methionine salvage. The gene is located at 9p21, a chromosome region often deleted in breast carcinomas, similar to CDKN2A, a recognized tumor suppressor gene. Several research groups have shown that MTAP acts as a tumor suppressor, and some therapeutic approaches were proposed based on a tumors´ MTAP status. We analyzed MTAP and CDKN2A gene (RT-qPCR) and protein (western-blotting) expression in seven breast cancer cell lines and evaluated their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 29 publications
3
21
0
1
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Based on the metabolic difference, blockade of de novo purine synthesis in MTAP-deficient tumors, in theory, might be a potent strategy to inhibit tumors without affecting normal cells. Several studies demonstrated MTAP-deficient tumor cells are more sensitive than MTAP-positive cells to purine synthesis inhibitors 7,14,15 . In breast cancer cell lines, the cytotoxic activity of 5-fluorouracil and methotrexate were increased after MTAP knockdown 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Based on the metabolic difference, blockade of de novo purine synthesis in MTAP-deficient tumors, in theory, might be a potent strategy to inhibit tumors without affecting normal cells. Several studies demonstrated MTAP-deficient tumor cells are more sensitive than MTAP-positive cells to purine synthesis inhibitors 7,14,15 . In breast cancer cell lines, the cytotoxic activity of 5-fluorouracil and methotrexate were increased after MTAP knockdown 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated MTAP-deficient tumor cells are more sensitive than MTAP-positive cells to purine synthesis inhibitors 7,14,15 . In breast cancer cell lines, the cytotoxic activity of 5-fluorouracil and methotrexate were increased after MTAP knockdown 15 . MTAP was often used to predict outcomes in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, approximately 15% of cancers exhibit homozygous deletions of the CDKN2a locus, which encodes for the tumor suppressor p16, with 80-90% of these tumors also exhibiting concurrent deletion of a proximal gene, MTAP, that encodes for the methionine salvage enzyme methylthioadenosine phosphorylase (1,2). A number of studies have investigated MTAP deletion as a possible collateral lethality and have identified vulnerabilities in this subset of cancers (3)(4)(5)(6)(7), with several investigating some of the effects of MTAP deletion on metabolism (8)(9)(10). However, a systematic comparison of the relative effects of MTAP deletion as it relates to other variables that shape metabolism is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency of this enzyme has been recently found in different types of neoplasms, mainly due to deletion of the 9p21 locus, and associated with increased tumor aggressiveness [1,[3][4][5]. Su et al (2014), in an immunohistochemistry (IHC) study of 99 lung cancer samples, demonstrated that MTAP was an independent marker of prognosis in patients with non-small-cell lung cancer [3].…”
mentioning
confidence: 99%